Republic of Kenya : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The CFAA had two key objectives, firstly to facilitate a common understanding by the Government of Kenya and development partners of the country's financial management arrangements in both the public and private sectors, identifying areas for improvement and reaching agreement amongst key stakeholders on how to take this forward. Secondly, to identify areas where accountability arrangements need to be strengthened and the risks that these may pose in relation to the use of public funds. Kenya's system of financial management in the public sector has some strengths, notably a sound code of financial regulations, the existence of a core of skilled top level managers, an updated budget framework, the computerization of a number of financial accountability functions as well as the powers and autonomy of the Controller and Auditor General (C&AG) rooted in the Constitution. In the private sector, the accountancy profession is well established and the Government has created an enabling environment for financial accountability through a solid legal framework. Nevertheless, the fiduciary risk in public spending is assessed as high. While a lack of compliance with established financial and procurement regulations have completely rendered many initiatives aimed at strengthening the control environment ineffective, issues of limited execution, inadequate monitoring, insufficient capacity and lack of enforcement also need to be resolved. The country's financial accountability framework, and therefore financial management, would be considerably more effective and the associated fiduciary risk mitigated, if these areas were strengthened. Consequently, it is envisaged that any kind of adjustment or programmatic lending in the immediate future would have to go hand in hand with significant improvements in public sector financial management.